WALCOM: algorithms and computation : 6th International Workshop, WALCOM 2012, Dhaka, Bangladesh, February 15-17, 2012. Proceedings - Nakano, Shin-ichi; Rahman, Md. Saidur (Lecture Notes in Computer Science, 2012)
This book constitutes the refereed proceedings of the 6th International Workshop on Algorithms and Computation, WALCOM 2012, held in Dhaka, Bangladesh, in February 2012. The 20 full papers presented together with 3 invited papers were carefully reviewed and selected from 50 submissions. The papers are grouped in topical sections on graph algorithms; computational geometry; approximation algorithms; graph drawing; string and data structures; and games and cryptography.